2017
DOI: 10.1016/j.tekhne.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

How managers use the balanced scorecard to support strategy implementation and formulation processes

Abstract: In the last twenty years the relationship between Management Control Systems (MCS) and strategy has become a relevant issue to management control investigation. This study aims to understand how managers use the Balanced Scorecard (BSC) to support the processes of implementation and formulation of strategy. The research adopts an exploratory case study approach and was conducted on a business unit of a large industrial Portuguese company.Results were analysed from the standpoint of Simons' four control levers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…The popularity of macs tools to support strategy has grown in recent years, the interest emanates from the developments of methods such as budgeting, the balanced scorecard (Ferreira, 2017), or activity-based costing.…”
Section: Management Accounting and Control Systems And Their Role In Organizationsmentioning
confidence: 99%
“…The popularity of macs tools to support strategy has grown in recent years, the interest emanates from the developments of methods such as budgeting, the balanced scorecard (Ferreira, 2017), or activity-based costing.…”
Section: Management Accounting and Control Systems And Their Role In Organizationsmentioning
confidence: 99%
“…This critical added value has been demonstrated in recent studies [5,25,31,65,66]. For example, [16,67] advocated the position that the BSC items are capable of promoting learning and the alignment of employees with the companies' strategy, provided that the same items are used in a dynamic and interactive way; Arasli et al (2019) [53,68,69] considered that the implementation of the BSC in organisations has a relevant influence on strategic decision-making processes and Dincer & Yuksel (2019) [37,70,71] proved that the use of the BSC reduces the subjectivity surrounding this process; Malagueño et al (2018) [72][73][74] postulated that companies using the BSC demonstrated greater capacity to implement innovations at the operational level. As for Quesado et al (2022) [31], the authors suggest that measurement of organisational performance through the BSC provides fundamental information for decision making, resource allocation, planning and control, influencing employee behaviour towards alignment with organisational objectives and also provides effective communication of corporate strategy [8] in order to influence people, processes and infrastructures with it [75][76][77].…”
Section: Synopsis On the Bscmentioning
confidence: 78%
“…The Balanced Scorecard fulfills the principles of structuring a managerial control system, as proposed by Otley [79], with key concepts such as goals, strategies, and plans; setting short-term goals; incentive and reward structures; and information feedback cycles. Owing to performance measurement, the Balanced Scorecard plays an essential role in many contemporary organizations, both in the analysis and implementation of strategy and in evaluating the achievement of organizational goals [7,8,42,55,80].…”
Section: Balanced Scorecard As a Methodologymentioning
confidence: 99%
“…Analysis of experiences of recent application of the BSC system in the public sector was presented by de Freitas et al [41]. Papers [42][43][44][45][46][47] are among the most prominent recent publications on organizational performance and the BSC system, where [43,46] consider the application of the BSC model in digital transformation.…”
Section: Previous Researchmentioning
confidence: 99%